Effects of microstructure and γ′ distribution on the hot deformation behavior for a powder metallurgy superalloy FGH96. Issue 23 (27th November 2014) - Zhang, Chi; Zhang, Liwen; Li, Mengfei; Shen, Wenfei; Gu, Sendong
Abstract: Abstract : Aiming to clarify the effects of initial states on hot deformation behavior of a powder metallurgy nickel-based superalloy FGH96, specimens in hot isostatic pressed (HIPed) and solution states were isothermally compressed in the temperature range of 1000–1150 °C and the strain rate range of 0.001–1.0 s −1 . It revealed that the flow behavior of FGH96 was dependent on the initial states, in which the deformation resistance was higher in the solution state than that in the HIPed state at evaluated temperatures, and the differences became less when the temperature was higher than the γ′ dissolution temperature. The calculated hot activation energy using peak stresses are 590 and 1285 kJ mol −1 for HIPed and solution specimens. Comparison with HIPed specimen, the efficiency of power dissipation (η) in solution specimen is less, and the optimum workability regime moves to higher temperatures. Cracking and in-grain shear bands were observed in the specimens when compressed in flow instability areas.